Efficacy and safety of dapagliflozin in Asian patients with type 2 diabetes after metformin failure: A randomized controlled trial*: 达格列净治疗接受二甲双胍治疗失败的亚洲2型糖尿病患者的疗效和安全性:一项随机对照研究. (9th January 2016) - Yang, Wenying; Han, Ping; Min, Kyung‐Wan; Wang, Bei; Mansfield, Traci; T'Joen, Caroline; Iqbal, Nayyar; Johnsson, Eva; Ptaszynska, Agata
Abstract: Background: Dapagliflozin, a highly selective sodium–glucose cotransporter 2 inhibitor, reduces hyperglycemia, body weight, and blood pressure in patients with type 2 diabetes (T2D). Methods: This randomized double‐blind placebo‐controlled parallel‐group 24‐week study assessed the efficacy, safety, and tolerability of dapagliflozin added to metformin in Asian patients with inadequately controlled T2D (HbA1c 7.5%–10.5%). Patients were randomized to receive placebo ( n = 145) or dapagliflozin 5 ( n = 147) or 10 mg ( n = 152). Results: Most participants were Chinese (86.0%), with a mean age of 53.8 years and mean T2D duration of 4.9 years; 92.1% completed the study. Adjusted mean HbA1c changes from baseline at Week 24 (primary endpoint) were −0.23%, −0.82%, and −0.85% in the placebo, dapagliflozin 5 and 10 mg groups, respectively, resulting in dapagliflozin 5 and 10 mg versus placebo differences of −0.59% and −0.62%, respectively (both P < 0.0001). Dapagliflozin 5 and 10 mg differences versus placebo were, respectively: –1.2 and −1.5 mmol/L for fasting plasma glucose; −1.1 and −1.8 kg for weight; and −2.3 and −2.7 mmol/L for 2‐h postprandial glucose (all P <0.0001). In the placebo, dapagliflozin 5 and 10 mg groups, respectively: adverse events (AEs) occurred in 52.4%, 52.4%, and 55.3% of patients; serious AEs occurred in 4.1%, 2.0%, and 2.0%; urinary tract infections occurred in 4.8%, 4.1%, and 6.6%; and genital infections occurred in 0%, 2.0%, and 1.3%. No AEs of pyelonephritis or renal failure occurred. Conclusions: Dapagliflozin 5 or 10 mg as add‐on to metformin was well tolerated in Asian patients with T2D and significantly improved glycemic control with the additional benefit of weight reduction. Abstract : Primary endpoint: change in HbA1c (%) by study week. Data are adjusted mean changes from baseline ±95% confidence intervals derived from analysis of covariance (last observation carried forward [LOCF]) and exclude data after rescue therapy. MET, metformin; PBO, placebo. Highlights: In Asian patients with type 2 diabetes, dapagliflozin added to metformin significantly improved glycemic parameters, compared with placebo added to metformin. In addition to improved glycemic control, dapagliflozin in combination with metformin reduced body weight and systolic blood pressure in this patient population. Treatment with dapagliflozin was well tolerated and associated with a low rate of hypoglycemic events.